Nursing Intervention for Incidence Phlebitis Prevention in Adult Patient: A Systematic Review - Albertina Dete Tabik; Abu Bakar; Ika Nur Pratiwi (Eduvest - Journal of Universal Studies, 2026)
Phlebitis refers to the inflammation or irritation of the vein wall, often caused by mechanical, chemical, or bacterial factors. Mechanical phlebitis is related to the action of the peripheral intravenous catheter (PIVC), chemical phlebitis arises from infusates or medications, and bacterial phlebitis is due to contamination at the insertion site or in the intravenous solution or tubing. Catheter-associated bloodstream infections (CABSI) can significantly increase healthcare costs, with treatment costs ranging from $3,000 to $56,000 per episode and prolonged hospital stays averaging 7 to 14 days (Marsh et al., 2024). This study, titled Nursing Intervention for Incidence Phlebitis Prevention in Adult Patient: A Systematic Review, aims to identify effective interventions that can be adopted by healthcare facilities, particularly in wards, to prevent phlebitis. This article analyzes data from six databases: Scopus, PubMed, ProQuest, ScienceDirect, Google Scholar, and Web of Science, focusing on articles published between 2019 and 2025. A total of 10 articles with randomized controlled trial (RCT) designs, scoring above 70% on the JBI assessment, were selected. The results indicate that moist heat therapy significantly improved vein visibility and palpability, reduced pain during cannulation, and increased first-attempt success to 93.3%. Clinically indicated catheter removal was found to be as effective as routine 96-hour replacement for preventing phlebitis.